(untitled) - Rubenstein, James M (Business Expert Press, 2014)
Ebook from IG Library ; The motor vehicle industry is one of the world's largest. More than 1 billion vehicles are in use around the world, and 80 million are produced and sold annually. Motor vehicles--including passenger cars, trucks, and commercial vehicles such as buses and taxis--are the principal means by which people and goods are transported within and among most communities in the world. This book details the history of the motor vehicle and of the leading carmakers. Inside, you'll learn just how cars are made and sold; the leading suppliers of parts that go into a car; the increasing role of government in regulating vehicles; and future challenges for the industry. The motor vehicle industry includes corporations that design, develop, and manufacture cars and trucks. These carmakers, such as Ford and Toyota, are among the world's most-familiar corporate brands. The motor vehicle industry also encompasses lesser-known businesses, including several thousand parts makers, tens of thousands of retailers, and specialized lending agencies. The importance of the motor vehicle industry transcends even its central role in the global economy. The industry was responsible for many of the fundamental innovations of 20th century production, such as corporate organization, manufacturing processes, and labor relations, as well as sales innovations including product branding and consumer financing. In the 21st century, the motor vehicle industry has been a leader in adopting new production strategies and expanding into new markets.
Keywords: Industry Profiles; Hồ sơ công nghiệp; Ngành công nghiệp ô tô và xe cơ giới